THE RELATIONSHIP OF ISLAMIC VALUES AND ORGANISATIONAL LEADERSHIP: A CASE STUDY OF MUSLIM EMPLOYEES IN MALAYSIA - Achour, Meguellati; Thaib, Lukman (Journal of Al-Tamaddun, 2015)
This study seeks to measure how Islamic values relate with organisational leadership in Malaysian Banks. The determinants of Islamic values included under this study are modesty, motivation, and beliefs. The researcher sampled 194 staff as respondents employed in banks in Kuala Lumpur, Malaysia. The sample consisted of 70 male and 124 female respondents with ages ranging from 20 to 60 years. The findings show that there is a significantly strong positive correlation between organisational leadership and Islamic values, organisational leadership and modesty, organisational leadership and motivation, as well as organisational leadership and beliefs. Furthermore, there is a strong and significant correlation between Islamic values and modesty, motivation, and beliefs.